Cancer in the head and neck region and its face under the perspective of users of a public reference hospital in Recife, state of Pernambuco, Brazil - Angélica Lopes Frade; Beatriz Santos Borges; Fátima Cristina Mendes Matos; Aurora Karla de Lacerda Vidal (Brazilian Journal of Otorhinolaryngology)
Objective: This study aimed to identify and analyze the difficulties experienced by head and neck (H&N) cancer patients, who are users of the Brazilian public health system (SUS), from their perspective of diagnosis to post-treatment. Methods: Qualitative case series carried out using individual semi- structured interviews. Data were collected from October 2019 to March 2020 and interpreted by content analysis. Results: Three categories emerged from the analysis: “difficulties in the diagnosis phase”, “conflicts experienced during treatment” and “post-treatment difficulties/sequelae”. Corroborating the literature, it was found that the difficulties faced by cancer patients are present in all stages of the disease: from access to prevention health services and diagnosis to post-treatment, influenced by late diagnosis, treatment side effects, and disease comorbidities. Conclusion: It is essential to carry out studies addressing changes in the family, professional and personal scope of cancer patients, aiming to provide them with comprehensive care and health professionals with understanding about what this disease represents in the life of these individuals. Level of evidence: Level IV.